Impact Assessment of the National Greening Program of the DENR: Scoping or Process Evaluation Phase - Institutional Component - Maria Paz G. Luna (Philippine Institute for Development Studies (PIDS), 2016)
The National Greening Program (NGP) comes after a dip in the country's forest cover and a decade after a large reforestation program was judged to be unsustainable. Large-scale reforestation globally has met with limited success but as a jump-start mechanism that carpet bombed large denuded areas with reforestation effort, the NGP seems to have succeeded in at least two of its measured metrics. As a bonus, the uniformity and strict monitoring of the program, both in survival rates and financial flows, can be used to clean up the Department of Environment and Natural Resources bureaucracy if complaints can be acted on swiftly, and results are communicated to complainants. To ensure efficiency and sustainability, a succeeding program would need to diversify methods based on scale, existing forest cover, and implementer's motivations; use strategic policy interventions and targeted protection measures; and be implemented by an organization with a clear reforestation and forest production mandate and with skills for dispute resolution, organizing, and efficient technology transfer. Digital media would also have to be taken advantage of for mapping, public buy-in, crowd-sourced strategies, and methods and transparency.
Keywords: 330; Reforestation; geo-tagging trees; forestry law enforcement; tree planting; forestry agency